TATA KELOLA ADMINISTRASI DESA KARANGMULYA: TANTANGAN DAN SOLUSI DI KECAMATAN BOJONGMANGU - Fadillah, Yusuf Naufal; Suryani, Elvira; Rofieq, Ainur (Universitas Islam 45 Bekasi, 2024)
Karangmulya Village, located in Bojongmangu District, faces significant challenges in administrative governance, impacting the quality of public services and community development. The primary issues identified include a lack of skilled human resources in village administration, low community participation in decision-making processes, and an unstructured and inefficient archival management system. This community engagement program employs observation, interviews, and socialization methods to analyze these challenges and formulate applicable solutions. Through socialization sessions involving expert speakers, it was found that enhancing the capacity of village officials through continuous training is essential to improving administrative efficiency and effectiveness. Additionally, the implementation of a more modern and structured archival management system is necessary to ensure transparency and ease of access to administrative data. Another key focus is the strategy to increase community participation through more inclusive and collaborative approaches, enabling residents to play an active role in village development. The results of this initiative indicate that targeted training and socialization efforts significantly enhance the administrative skills of village officials while also fostering greater community involvement in governance. By implementing these strategic measures, it is expected that the administrative governance of Karangmulya Village can be optimized, leading to improved public services and contributing to overall community welfare.